Coastline Dynamics and Raising Landform: A Geo-informatics Based Study on the Bay of Bengal, Bangladesh - Nur Hussain; Ebadullah Khan (Indonesian Journal of Geography, 2018)
The southern part of Bangladesh is bounded by the Bay of Bengal. Three major river systems such as; Brahmaputra-Jamuna, Ganges-Padma and Surma-Kusiara have been developed the Ganges-Brahmaputra-Meghna (GBM) floodplain, this are 80% area of Bangladesh. These rivers carry huge sediments from upper Himalayan region during at monsoon period. On the contrary, as the costal part of Bangladesh is open to the sea, so high wave actions, strong wind flow, tidal actions are prevailing here. Consequently, coastline of this part is unstable and dynamic. Coastline change dynamics is significant for disaster management, coastal planning and environmental management. For the delineation of coastline identification, Rennell’s map (1776), Landsat MSS (1976) and Landsat OLI (2016) images have been interpreted using the tools of Remote Sensing Technology and Geographic Information System (GIS) of Geo-informatics. During 240 years from 1776 to 2016 about 3892 km2 landform have been raised in coastal area of Bangladesh.